Pengaruh Harga dan Promosi terhadap Kepuasan Konsumen pada Usaha Travel Mobil - Maria Ulfa; Selviani Selviani (AL-Muqayyad, 2022)
This study aims to determine the significant effect of price and promotion on consumer satisfaction in an Islamic perspective. In this study, the research subjects were consumers of PT. Tsalatsa Putri Abadi Travel while the object of research is the effect of price and promotion on consumer satisfaction at PT. Tsalatsa Putri Abadi Travel. This type of research is quantitative research. By using multiple regression analysis method. The results of the regression show that the t-count value of the X1 variable is 3.543 and the t-count of the X2 variable is 20,419 > from t table 1,970 and the calculated F value is 284,731 > from F table 3,04 with a significant value of 0.000 at a significant level of 0.05 . Thus, it can be concluded that prices and promotions have a significant positive effect on customer satisfaction by 72.7% in the car travel business of PT. Tsalatsa Putri Abadi Travel Tembilahan. Where are the prices and promotions from PT. Tsalatsa Putri Abadi Travel Tembilahan is categorized as "good".